Patients' perspectives on factors affecting their involvement in decision-making on oral anticoagulant therapy for stroke prevention in non-valvular atrial fibrillation. (26th March 2021) - Medlinskiene, K; Richardson, S; Petty, D; Stirling, K; Rattray, M; Fylan, B
Abstract: Introduction: Acknowledging patients' preferences and addressing their concerns is thought to improve patients' satisfaction with consultations, resulting in improved adherence and health benefits [1]. Adherence to oral anticoagulant (OA) therapy in non-valvular atrial fibrillation (NVAF) is crucial to prevent AF-related strokes. Previous research on anticoagulation in NVAF indicated that decision-making was dominated by prescribers, but patients offered several therapy options reported being involved [2]. Identifying the patient's perspective on factors affecting their involvement could help to deliver more patient-centred care in the management of AF. Aim: To explore patients' perspectives and experiences concerning factors affecting their involvement in decision-making about OA therapy for stroke prevention in NVAF. Methods: Semi-structured face-to-face interviews were conducted with patients in three health economies in the North of England between August 2018 and April 2019. An interview topic guide based on narrative review findings [2] was developed and refined by a Patient and Public Involvement (PPI) group to ensure clarity. Theoretical sampling was used to recruit adults (>18 years) diagnosed with NVAF, prescribed OA (vitamin K antagonist or direct oral anticoagulant (DOAC)), and able to give written consent. Up to 30 potential participants were approached by a member of their direct care team (nurse or pharmacist) in secondary and primary care anticoagulation or arrhythmia clinics. PPI members recruited patients from a local patient support group. Data collection continued until data saturation was achieved. Audio recorded interviews were transcribed verbatim and analysed using the Framework method. Results: A total of 21 patient with median (IQR) age of 73 years (65–78 years) were interviewed. Eleven patients took DOACs. The median (IQR) time of taking OA was 3 years (4 weeks-7 years), warfarin 7 years (3–9 years) and DOAC 1 year (4 weeks-4 years). Interviews lasted between 15 and 48 minutes (average 27 minutes). Three themes were identified during analysis (Figure 1). Patients described therapy decisions being made by just the clinician, jointly with the clinician, and in few cases by the patient alone. The lack of involvement resulted from patients perceiving that there was only a choice between accepting and refusing the therapy, and clinician's role was to make decisions. Limited consultation times, lack of continuous relationship with a clinician and knowledge about OAs options discouraged patients from being involved and some patients reported difficulties with the prescribed therapy. Patients that were involved considered safety of therapy options and impact on daily life. Conclusions: Limited consultation time, patient's perception of clinician's role, quality of patient-clinician relationship, and patients' awareness of therapy options were main factors influencing the level of patient involvement in the decision-making. Support from both organisation and clinicians (e.g., longer consultations, availability of different therapy options) is needed to facilitate greater patient involvement, which could prevent difficulties encountered by some patients. The main strength of this study was recruitment of participants from three health economies differing in anticoagulation service provision models, which enabled greater insight into potential barriers. However, the sample was lacking ethnic diversity and could have potential of recall bias. References: 1. Shay LA and Lafata JE. (2015). Where is the evidence? A systematic review of shared decision making and patient outcomes. Medical Decision Making. 35 (1): 114–131. 2. Medlinskiene K, Petty D, Richardson S and Stirling K. (2018) Are patients with non-valvular atrial fibrillation involved in decision-making about oral anticoagulants? A literature review. International Journal of Pharmacy Practice. 26 (Suppl. 1): 42–43.